2017
DOI: 10.1021/acs.jpca.7b06621
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Behavior of Noise in Asynchronous Spectra in Generalized Two-Dimensional (2D) Correlation Spectroscopy and Application of Butterworth Filter in the Improvement of Signal-to-Noise Ratio of 2D Asynchronous Spectra

Abstract: The behavior of noise in asynchronous spectrum in generalized two-dimensional (2D) correlation spectroscopy is investigated. Mathematical analysis on the noise of 2D spectra and computer simulation on a model system show that the fluctuation of noise in a 2D asynchronous spectrum can be characterized by the standard deviation of noise in 1D spectra. Furthermore, a new approach to improve a signal-to-noise ratio of 2D asynchronous spectrum by a Butterworth filter is developed. A strategy to determine the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Here, n = 201. Two-dimensional correlation spectroscopy developed by Noda is a powerful spectral analysis method to analyze complex spectral intensity variation obtained successively under certain form of perturbation, such as temperature, pressure, or even concentration, and so on [12,33]. In two-dimensional correlation spectroscopy, a group of spectral data is transformed into a correlation intensity map defined by two independent spectral axes.…”
Section: Spectral Angle and Two-dimensional Correlation Spectroscopymentioning
confidence: 99%
“…Here, n = 201. Two-dimensional correlation spectroscopy developed by Noda is a powerful spectral analysis method to analyze complex spectral intensity variation obtained successively under certain form of perturbation, such as temperature, pressure, or even concentration, and so on [12,33]. In two-dimensional correlation spectroscopy, a group of spectral data is transformed into a correlation intensity map defined by two independent spectral axes.…”
Section: Spectral Angle and Two-dimensional Correlation Spectroscopymentioning
confidence: 99%
“…In our previous work, we demonstrated that the noise fluctuation could be reflected by the standard deviation of a 2D asynchronous spectrum at a given position in statistical analysis. 35 Herein, we adopt the following procedure to retrieve the value of standard deviation.…”
Section: Resultsmentioning
confidence: 99%
“…41 In our previous work, we used a Butterworth filter to suppress noise in 2D spectra. 35 In noise reduction approaches, an unavoidable problem is signal distortion, which might mislead the analysis of 2D spectra, which is why we emphasized that the balance should be maintained between noise reduction and suppression of signal distortion. In the second aspect, enhancement of the signal part can be realized with a modification of the approach to generate 2D spectra.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent decades, many applications including studies on intermolecular interactions using 2D-COS have been reported. 2036 We propose an orthogonal sample design scheme (OSD) 37 and relevant techniques. 3841 In these approaches, interference portion in cross peaks, which has no relationship with intermolecular interaction, can be thoroughly eliminated via the product of orthogonal vectors.…”
Section: Introductionmentioning
confidence: 99%